Đánh giá sự phát triển tư duy khái quát hóa qua trò chơi toán học ở trẻ 5-6 tuổi: Một nghiên cứu lí luận - Đỗ, Thị Minh Nguyệt; Nguyễn, Thị Hiền (Tạp chí Giáo dục, 2025)
Generalization thinking is a fundamental cognitive skill that should be nurtured from an early age to form the foundation for academic reasoning and problem-solving in preschool children. In the context of current educational innovation, the lack of appropriate assessment tools for this skill poses a significant challenge. This article establishes the theoretical foundation for assessing the development of generalization thinking through mathematical games in children aged 5-6, based on the analysis of contemporary educational theories such as those of Piaget, Vygotsky, Bruner, and Gardner. The findings indicate that mathematical games serve as an effective pedagogical environment to assess and enhance generalization thinking in a natural and developmentally appropriate manner. The author recommends designing an assessment model that integrates both qualitative and quantitative approaches, and proposes future research directions to develop concrete models and empirically test their effectiveness in early childhood.